The long arm of the law : classic police stories - Edwards, Martin, 1955- (British Library crime classics., 2017)
In classic British crime fiction, dazzling detective work is often the province of a brilliant amateur - whereas the humble police detective cuts a hapless figure. The twelve stories collected here strike a blow for the professionals, with teasing mysteries to challenge a hard-working police officer's persistence and scrupulous attention to detail. As in his previous anthologies for the British Library Crime Classics series, Martin Edwards introduces readers to fascinating neglected gems of British crime writing as well as uncovering lesser-known stories by the great novelists of the golden age. Each of these stories combines realism with entertainment, skilfully blending the conduct of a criminal investigation with a compelling murder-mystery plot.